Application and Research of Analytical Chemistry Technology in Food Safety Testing. Issue 3 (March 2021) - Kang, Hongling; Liu, Yinan; Hu, Shuang; Liu, Xin; Wang, Man; Sun, Wan; Chen, Lihua; Yan, Rong
Abstract: Food safety problems occur frequently, and the food safety problems of major enterprises are continuously reported. Therefore, food safety quality and how to test food safety have become the focus of people's attention. The technical testing of food safety is mainly achieved through chemical means, but with the continuous development of science and technology, the disadvantages of chemical testing technology continue to appear, so how to improve the chemical testing technology has become a difficult problem to be overcome in the technical field. The thesis focuses on various chemical technologies in food safety testing, such as electrochemical immunosensors, liquid chromatography detection, pigment rapid testing instruments, nucleic acid aptamers, etc., and selects several items for detailed description.